The effects of participation in European competitions on the domestic competitiveness of Polish football clubs - Szczepan Kościółek (International Entrepreneurship Review, 2022)
Objective: The objective of this study was to establish whether participation in European football competitions affects the sports performance of Polish football clubs in the domestic league. Accordingly, negative short-term effects and positive medium-term effects were hypothesized.